Kandungan flavonoid, α-Tokoferol, aktivitas antioksidan pada food bar tepung mocaf, tepung daun kelor, dan tepung ikan kembung sebagai potensi antihipertensi - Salwa Yasmin; Ibnu Malkan Bakhrul Ilmi (Poltekkes Kemenkes Aceh, 2026)
Background: Hypertension is a leading global cause of death associated with oxidative stress. Antioxidants help prevent oxidative stress, potentially reducing the risk of hypertension. Food bars from mocaf flour, moringa leaf flour, and mackerel flour have potential to be developed as functional foods due to their flavonoid, α-tocopherol, and antioxidant activity content.Objectives: This study analyzed the total flavonoid content, α-tocopherol, and antioxidant activity in food bars as potential antihypertensive functional foods.Methods: This study used an experimental method with a completely randomized design and three formulas. The study was conducted from June to August at three different locations. Flavonoids were analyzed using AlCl₃ UV-Vis spectrophotometry, α-tocopherol using HPLC, and antioxidant activity using the DPPH method. The results of the measurements were analyzed descriptively, followed by a normality test, with a one-way ANOVA and Duncan's test if normally distributed, and Kruskal-Wallis and Mann-Whitney tests if not normally distributed.Results: The results showed that Among the formulas, the highest total flavonoid content was in F1 (0.71 ± 0.01 mg/g), and the highest α-tocopherol content was in F2 (8.62 ± 0.23 mg/100 g). The strongest antioxidant activity among the three formulas was observed in F1 (1414.105 ± 0.84 mg/L). Based on the Shapiro-Wilk test, the three contents tested were normally distributed (p>0.05), but only the antioxidant activity and α-tocopherol showed a significant difference (p<0.05).Conclusion: Food bars made from mocaf flour, moringa leaf flour, and mackerel flour contain flavonoids and α-tocopherol, which contribute to antioxidant activity, making them potential functional foods with antihypertensive properties.